EFFECTS OF A PAIN MANAGEMENT AND BOWEL MOTILITY ENHANCEMENT PROTOCOL IN PATIENTS FOLLOWING URGENT ABDOMINAL SURGERY - Suwanmongkol, Rattiyakorn; Chatchumni, Manaporn; Namvongprom, Ampaporn (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2025)
This quasi-experimental study aimed to compare pain scores, bowel motility, length of hospital stay, and medical expenses between two groups of patients after urgent abdominal surgery: one receiving a developed pain management and bowel motility enhancement protocol, and the other receiving standard postoperative care. The sample consisted of 56 male patients admitted to Male Surgical Ward 1 at King Narai Hospital in Lopburi Province, evenly divided into experimental and control groups (28 each). The control group received routine postoperative care, while the experimental group received an intervention protocol involving pain medication with deep breathing exercises, gum chewing, and mobilization at 24-, 48-, and 72-hour post-surgery. Data collection tools included personal data forms, pain score records, bowel motility assessments, hospital length of stay, and treatment cost records. Data were analyzed using descriptive statistics and non-parametric tests including the Mann-Whitney U test, Chi-square test, Friedman test, and Spearman’s rank correlation coefficient. The results showed that the experimental group’s median pain scores at 24-, 48-, and 72-hour post-surgery were 6.33 (moderate), 4.00 (moderate), and 1.33 (mild), respectively, significantly lower than those in the control group (Z = 118.50, 73.00 and 27.00; p < .05). Median bowel motility scores in the experimental group were 5.83 (moderate), 3.66 (high), and 1.33 (high), which showed a significant improvement over those of the control group (Z = 2.50, 27.50 and 58.00; p < .05). However, there were no statistically significant differences between the two groups in terms of hospital stay duration or treatment costs (p > .05). The findings of this study support that the developed practice guidelines can be appropriately applied to this patient group, particularly in clinical settings aiming to reduce postoperative pain and accelerate bowel function recovery.